If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -5(3t + -4) = 8 + -1(2t + 11) Reorder the terms: 16 + -5(-4 + 3t) = 8 + -1(2t + 11) 16 + (-4 * -5 + 3t * -5) = 8 + -1(2t + 11) 16 + (20 + -15t) = 8 + -1(2t + 11) Combine like terms: 16 + 20 = 36 36 + -15t = 8 + -1(2t + 11) Reorder the terms: 36 + -15t = 8 + -1(11 + 2t) 36 + -15t = 8 + (11 * -1 + 2t * -1) 36 + -15t = 8 + (-11 + -2t) Combine like terms: 8 + -11 = -3 36 + -15t = -3 + -2t Solving 36 + -15t = -3 + -2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '2t' to each side of the equation. 36 + -15t + 2t = -3 + -2t + 2t Combine like terms: -15t + 2t = -13t 36 + -13t = -3 + -2t + 2t Combine like terms: -2t + 2t = 0 36 + -13t = -3 + 0 36 + -13t = -3 Add '-36' to each side of the equation. 36 + -36 + -13t = -3 + -36 Combine like terms: 36 + -36 = 0 0 + -13t = -3 + -36 -13t = -3 + -36 Combine like terms: -3 + -36 = -39 -13t = -39 Divide each side by '-13'. t = 3 Simplifying t = 3
| 4x=ln(8) | | 2sin^2x+sin(x)=1 | | 3w(2p+7)=15(p-4) | | (11x+4)+(8x+5)= | | b=1/2gr | | y=2(1.125)-1 | | 2x+3(2x-1)=6 | | y=x-6/2 | | (x+y)(x^2-y^2)-(x^2-y^2)= | | y=-3(2.25)+6 | | 2/15(x-2y-5z) | | 12x-7+x=3x-1 | | 3A-4B+7C=28 | | 2l=2w | | 2.25+3y=6 | | 4y=-8x-20 | | 2x^2-5y^2+4x-15y+20=0 | | x^2+3(x^2-1)=6 | | f(x)=14x^3+9x^2-2 | | 1.8+75=15.8 | | -39=6+5x | | 16(6z+2)=-8(8z-20) | | 5t-1.7=82 | | xlogy=ylogx | | 3x+.5=6 | | 3n+6-2n=2(n-7) | | 3x+.5=-6 | | 9/6=×/8 | | 3x+.6=-6 | | 4(3b-4)=8b-12 | | 0=t^2-7t+4 | | x^3-1=20 |